Grip strength is a predictor of bone mineral density among adolescent combat sport athletes - Nasri, R.; Zrour, S. H.; Rebai, H.; Najjar, M. F.; Neffeti, F.; Bergaoui, N.; Mejdoub, H.; Tabka, Z. (Journal of Clinical Densitometry, 2013)
The aim of this study was firstly to investigate the correlation between bone parameters and grip strength (GS) in hands, explosive legs power (ELP), and hormonal parameters; second, to identify the most determinant variables of bone mineral density (BMD) among adolescent combat sport athletes. Fifty combat sport athletes aged 17.1±0.2 yr were compared with 30 sedentary subjects matched for age, height, and pubertal stage. For all subjects, the BMD in deferent sites associated with anthropometric parameters were measured by dual-energy X-ray absorptiometry. The growth hormone (GH) and testosterone (TESTO) concentrations were tested. The GS in dominant (GSDA) and nondominant arms (GSNDA) and ELP were evaluated. All BMD measured were greater in athletes than in sedentary group (p<0.01). The GS and ELP showed higher values in athletes than in sedentary group (p<0.01). The BMD in all sites were correlated with weight, but without correlation with height. The GSNDA and ELP were significantly correlated with BMD of both spine and legs. The GH was correlated with the BMD of whole body and spine (p<0.05). The TESTO was only correlated with BMD of the arms (p<0.01). The best predictor of BMD measurements is GSNDA. This study has proved the osteogenic effect of combat sports practice, especially judo and karate kyokushinkai. Therefore, children and adolescent should be encouraged to participate in combat sport. Moreover, it suggested that the best model predicting BMD in different sites among adolescent combat sports athletes was the GSNDA.